Public presentation anxiety: studies cases concerning public presentation anxiety of students prospective English teacher - Nasir, Nasir (Gema Wiralodra, 2023)
Anxiety with a reasonable intensity can be considered a positive value as motivation. Still, if the power is high and adverse, it can cause harm and can interfere with the physical and psychological state of the student concerned, even his learning achievement. This research is focused on semester II students of the 2023 FKIP Unwir English Language Education Program anxiety during public speaking or presentations. This study used a qualitative approach. The type of research used is a case study. Data collection was carried out by distributing questionnaires to 20 students. The study is presented in the form of a descriptive analysis. The results of this study indicate that the anxiety of students presenting in public is caused by, among others: (1) the innate nature of not being able to speak and being nervous when doing it, (2) lack of confidence, (3) lack of understanding of the material to be presented, (4) fear what was conveyed was wrong, (5) Getting questions that were difficult to answer, (6) Breaking out in cold sweat and tremors, (7) Watched by many people, (8) Brain fog for no reason, (9) There is painful criticism, (10). Fear of being laughed at by friends.